Active Layer Dynamics Near Norilsk, Taimyr Peninsula, Russia - Valery I. Grebenets; Vasily A. Tolmanov; Dmitry A. Streletskiy (Geography, Environment, Sustainability)
This paper provides information on active layer thickness (ALT) dynamics, or seasonal thawing above permafrost, from a Circumpolar Active Layer Monitoring (CALM) site near the city of Norilsk on the Taimyr Peninsula (north-central Siberia) and the influences of meteorological and landscape properties on these dynamics under a warming climate, from 2005 to 2020. The average ALT in loamy soils at this 1 ha CALM site over the past 16 years was 96 cm, higher than previous studies from 1980s conducted at the same location, which estimated ALT to be 80 cm. Increasing mean annual air temperatures in Norilsk correspond with the average ALT increasing trend of 1 cm/year for the observation period. Active layer development depends on summer thermal and precipitation regimes, time of snowmelt, micro-landscape conditions, the cryogenic structure (ice content) of soils, soil water content leading up to the freezing period, drainage, and other factors. Differences in ALT, within various micro landscape conditions can reach 200% in each of the observation periods.